Iron limitation differentially affects viral replication in key marine microbes - Charmaine C. M. Yung; Rachel L. Kelly; Kathryn M. Kauffman; Brady R. Cunningham; Amy E. Zimmerman; Alexandra Z. Worden; Seth G. John (Proceedings of the National Academy of Sciences, 2025)
Viral lysis accounts for much of microbial mortality in the ocean, and iron (Fe) is a critical micronutrient that can limit phytoplankton growth. However, interactions between Fe nutrition of microbes, including both heterotrophic bacteria and phytoplankton, and viral lysis are not well known. Here, we present viral infection dynamics under Fe-limited and Fe-replete conditions for isolates of three types of marine picoplankton, the photosynthetic picoeukaryote Ostreococcus , the cyanobacterium Synechococcus , and the heterotrophic bacterium Vibrio . Iron limitation of Ostreococcus resulted in slowed growth and reduced viral burst sizes; this is similar to prior results from studies of larger eukaryotic phytoplankton, where reduced viral replication under Fe limitation is attributed to the viral reliance on host metabolism and replication machinery. Fe limitation of one Vibrio impacted dynamics of its virus similarly, lengthening the latent period before infected cells burst to release new viruses, and reducing the number of infective particles released upon lysis. In contrast, for another Vibrio isolate, Fe limitation had no discernible effect on replication of its virus. Furthermore, dynamics of three cyanophages that infect the same Synechococcus isolate were not affected by Fe limitation of the host, either in terms of latent period or burst size. The results show that some marine viruses, particularly cyanophages, can replicate efficiently even when host growth is compromised. These findings have implications for marine ecology and carbon cycling in Fe-limited regions of the global ocean.